2016
DOI: 10.1093/ageing/afw119
|View full text |Cite
|
Sign up to set email alerts
|

Age- and sex-related differences in use of guideline-recommended care and mortality among patients with incident heart failure in Denmark

Abstract: older patients with HF were less likely to receive guideline-recommended processes of care, irrespective of sex. Lower level of care may contribute to an excess mortality observed among the older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…28,29 Further, there may be a dose-response association between the fulfilment of performance measures and mortality. 30 Our analyses revealed a gap in the quality of HF care provided by the Danish Healthcare system regardless of the causal mechanisms. We demonstrated that living alone was associated with a lower chance of receiving all HF care processes except treatment with MRA.…”
Section: Socioeconomic Factors and Composite Scores For Process Performance Measuresmentioning
confidence: 72%
See 1 more Smart Citation
“…28,29 Further, there may be a dose-response association between the fulfilment of performance measures and mortality. 30 Our analyses revealed a gap in the quality of HF care provided by the Danish Healthcare system regardless of the causal mechanisms. We demonstrated that living alone was associated with a lower chance of receiving all HF care processes except treatment with MRA.…”
Section: Socioeconomic Factors and Composite Scores For Process Performance Measuresmentioning
confidence: 72%
“…ACEI/ARB) and mortality and readmission among patients with HF, while other studies have not found this association 28,29 . Further, there may be a dose–response association between the fulfilment of performance measures and mortality 30 …”
Section: Discussionmentioning
confidence: 93%
“…This study also demonstrates that HF is a disease of the elderly and does not exist in isolation [ 21 , 22 ]. There is some evidence that older patients with HF are less likely to receive guideline-recommended care [ 23 ]. However, most current HF guidelines globally are disease specific and the trials on which they are based often excluded patients with multimorbidity [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, the trial population has been younger than in the real world; moreover, women have usually been underrepresented in all HF clinical trials. 5 , 6 Therefore, in this study, we studied how different levels of adherence to GDMT affect the risk of mortality in patients with HF across the LVEF spectrum in a real‐world clinical setting.…”
Section: Introductionmentioning
confidence: 99%